Psychic Shackles Violence in Women and Children in the District Grobogan - Kurnianingsih, Marisa; Absori, Absori; Sakti, Johan Cahya Kusuma (Universitas Islam Negeri Walisongo Semarang, 2021)
All forms of violence against women and children in the household are violations of human rights and crimes against human dignity as well as forms of discrimination that must be abolished. However, the psychological violence that occurs in the community, which as of this writing is in Grobogan Regency, is still difficult to find the exact number and is hampered in the process of proving it. The method used in this research is sociological juridical. This paper aims to determine the regulation of psychological violence itself that has been applied in Indonesia and then to describe the legal culture of the community against the occurrence of psychological violence. Basically, the concept of psychological violence is commonly found in the law on the elimination of domestic violence and the law on child protection. It is society habits if there is a psychic occurrence are still in doubt and consider the problem to be a private family problem, even if it is considered a light and embarrassing thing to be disclosed as a form of violence.[]Segala bentuk dari kekerasan terhadap perempuan dan anak dalam rumah tangga merupakan pelanggaran hak asasi manusia, kejahatan terhadap martabat kemanusiaan serta bentuk diskriminasi yang seharusnya dihapuskan. Namun kekerasan psikis yang terjadi di masyarakat yang pada tulisan ini di Kabupaten Grobogan, masih sulit ditemukan jumlah pastinya serta terganjal pada proses pembuktiannya. Metode yang digunakan dalam penelitian ini adalah yuridis sosiologis. Maka tulisan ini bertujuan untuk mengetahui pengaturan dari kekerasan psikis itu sendiri yang telah berlaku di Indonesia kemudian mendiskripsikan budaya hokum masyarakat terhadap terjadinya kekerasan psikis. Pada dasarnya konsepsi kekerasan psikis bias ditemukan didalam undang-undang tentang penghapusan kekerasan dalam rumah tangga dan undang-undang perlindungan anak. Kebiasaan masyarakat jika terjadinya psikis masih ragu dan menganggap masalah tersebut masih merupakan masalah privat keluarga bahkan dianggap hal yang ringan dan memalukan untuk diungkap sebagai bentuk kekerasan.